Trismus in Face Transplantation Following Ballistic Trauma. Issue 4 (June 2018) - Krezdorn, Nicco; Alhefzi, Muayyad; Perry, Bridget; Aycart, Mario A.; Tasigiorgos, Sotirios; Bueno, Ericka M.; Green, Jordan R.; Pribaz, Julian J.; Pomahac, Bohdan; Caterson, Edward J.
Abstract : Background: Trismus can be a challenging consequence of ballistic trauma to the face, and has rarely been described in the setting of face transplantation. Almost half of all current face transplant recipients in the world received transplantation to restore form and function after a ballistic injury. Here we report our experience and challenges with long standing trismus after face transplantation. Methods: We reviewed the medical records of our face transplant recipients whose indication was ballistic injury. We focused our review on trismus and assessed the pre-, peri- and postoperative planning, surgery and functional outcomes. Results: Two patients received partial face transplantation, including the midface for ballistic trauma. Both patients suffered from impaired mouth opening, speech intelligibility, and oral competence. Severe scarring of the temporomandibular joint (TMJ) required intraoperative release in both patients, and additional total condylectomy on the left side 6 months posttransplant for 1 patient. Posttransplant, both patients achieved an improvement in mouth opening; however, there was persistent trismus. One year after transplantation, range of motion of the jaw had improved for both patients. Independent oral food intake was possible 1 year after surgery, although spillage of liquids and mixed consistency solids persisted. Speech intelligibility testing showed impairments in the immediate postoperative period, with improvement to over 85% for both patients at 1 year posttransplant. Conclusions: Ballistic trauma to the face and subsequent reconstructive measures can cause significant scarring and covert injuries to structures such as the TMJ, resulting in long standing trismus. Meticulous individual planning prior to interventions such as face transplantation must take these into account. We encourage intraoperative evaluation of these structures as well as peri- and postoperative treatment when necessary. Due to the nature of the primary injury, functional outcomes after face transplantation in these patients may differ substantially from those of other indications.